Faktor Yang Berhubungan Terhadap Akses Pelayanan Kesehatan Di Puskesmas Seko Desa Padang Raya (Window of Public Health Journal, 2025)
Access to health services in Indonesia is still a problem. This is influenced by the fact that health facilities in Indonesia are pretty numerous, but their distribution is not evenly distributed. This impacts the ease of access and provision of health services. Based on the results of observations conducted by researchers, the geographical access that affects access to health services at the Seko Health Center includes the condition of the road infrastructure to the Seko Health Center in an unsuitable condition, physical obstacles such as public transportation to the Health Center. The utility of the Health Center in the physical condition of the Health Center building is poor and requires renovation, and the availability of human resources is inadequate. This study aims to determine the factors that affect access to health services at the Seko Health Center. The type of research is quantitative with a cross-sectional study approach. The sample size used was 220 respondents. The analysis was carried out univariately and bivariately using the chi-square test with a significance level of ρ =